Studi Literatur Keamanan dan Privasi Data Sistem Cloud Computing Pada Platform Google Drive - Zulkarnaim Masyhur; Adhy Rizaldy; Patmayanti Kartini (Journal Software, Hardware and Information Technology, 2021)
In today's era, we can do mobilization activities anytime and anywhere. Especially with the cloud computing system that makes it easy to interact from one computer to another without consuming a lot of money. This allows us to access data and information from computers or accounts that are connected. Google Drive is a data storage and synchronization service provided by Google. Where every user can use cloud computing in the form of file sharing and editing collaboration. The purpose of this paper is to find out how the challenges and solutions for data security and user privacy are on the Google Drive platform.